ANALYSIS OF THE IMPACTS OF ICMS ON THE PRODUCTIVE CHAINS OF SMALL BRAZILIAN STATES - THE CASE OF GOIÁS AND ITS CLUSTERS - Almeida, Wilson de Jesus Beserra de; Hsiang, Antonio (Revista Valore, 2021)
This article proposes to analyze the production chains of Brazilian states regarding the taxation of the Tax on Circulation of Goods and Services (ICMS) levied on Electronic Commerce (e-commerce) by the final consumer, who is not the taxpayer, through of interstate operation. Therefore, this is a comparative study of the rules and incidence of this tax at the national and international level, as well as the conflicts generated by federative entities, forming a type of "fiscal war", as a result of the application of the "origin principle", which probably no longer serve Federation purposes. The analysis addresses the importance of this new form of commerce, from the description of the evolution of e-commerce, as well as the delimitation of advances and perspectives for this type of commerce. Special focus is given to the economic impact due to the current tax collection model on consumer states, notably the state of Goiás, showing its influence on the deepening of regional inequalities. What was found was that the globalization process, including technological innovation and the consequent modernization of the economy, imposed new challenges and an urgent need for constitutional and legal adjustment of the National Tax System. This is evident in the STF decision regarding the grounds used in the declaration of unconstitutionality of the Protocol of ICMS 21/2011 that deals with the matter, however, some of them deserve a deep reflection. The maintenance of this situation in fact favors the fiscal imbalance of the states and compromises the federative pact for a possible violation of constitutional principles. The new Constitutional Amendment (EC 87/2015) may have been the first step in a necessary transition from the rule of origin to the rule of destination, advocated by this thesis.